2023
DOI: 10.1002/ejp.2096
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Parkinson's disease: Current mechanism and management updates

Abstract: The aim of this comprehensive review was to provide an overview of pain in Parkinson's disease (PD) by identifying different clinical features and potential mechanisms, and presenting some data on the evaluation and management of pain in PD. PD is a multifocal degenerative and progressive disease, which could affect the pain process at multiple levels. Pain in PD has a multifactorial aetiology, with a dynamic process based on pain intensity, complexity of symptoms, pain pathophysiology and presence of comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 181 publications
0
8
0
Order By: Relevance
“…This review includes literature about nonpharmacological pain management that can be provided by allied health; therefore, deep brain stimulation is not included. For a comprehensive summary of deep brain stimulation for pain management, please refer to the previous reviews [4,5]. Literature for inclusion in this review was identified by each author from personal libraries and resources.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This review includes literature about nonpharmacological pain management that can be provided by allied health; therefore, deep brain stimulation is not included. For a comprehensive summary of deep brain stimulation for pain management, please refer to the previous reviews [4,5]. Literature for inclusion in this review was identified by each author from personal libraries and resources.…”
Section: Methodsmentioning
confidence: 99%
“…This type of pain is variable in presentation, can be difficult to localize and fluctuates in intensity [24]. Changes in the central nervous system [4,28,33] may contribute to nociplastic pain in PwP. It is important to note that while these pain types all have their own definitions, in practice many people demonstrate features consistent with more than one pain type and many people with chronic pain will have a nociplastic component [3].…”
Section: Pain In Parkinson's Diseasementioning
confidence: 99%
See 3 more Smart Citations